Pengembangan Modul Bimbingan dan Konseling untuk Pencegahan Bullying di Sekolah - Yandri, Hengki; Daharnis, Daharnis; Nirwana, Herman (Universitas Negeri Padang, 2013)
This research aims to formulate guidance and counseling module to prevent bullying at school and to describe the level of applicability used by counselor. The method used was ADDIE model development. The subjects of the research consisted of guidance and counseling expert and the intended target of the module (counselor), chosen through purposive sampling. The instruments used were questionnaire and focus group discussion (FGD). The data were analyzed descriptively. The results showed that prototype modules developed to prevent bullying at school is applicable used by the counselor and those modules can be utilized by counselor to prevent bullying at school.